A QoS aware, multi-agent based approach to semantic web service composition - Garg S.K.; Mishra R.B. (My University, 2025)
A semantic web service composition system can be considered as a multi-agent system, in which each of the agent act as a component service provider. In the service composition process, selecting most appropriate service for performing a task is considered to be one of the important aspects. This paper proposes a multi-agent based semantic web service composition process. The process presented deals with some untouched issues in composition process. The work also presents a novel selection model based on quality of service (QoS) based rating of service providers. © 2008 IEEE.